PENGARUH EKONOMI MAKRO TERHADAP INDIKATOR PERGERAKAN (INDEKS) HARGA SAHAM - Yusup Hari Subagya (STIE St. Pignatelli Surakarta, 2020)
The purpose of this research activity is to find out how the macroeconomic influence on the indicators of movement (index) of stock prices on the IDX. The research method uses multiple linear regression analysis and in the form of quantitative descriptive data, sampling with a sampling technique in the form of purposive sampling from publication data from 2009-2019. The results showed that inflation and interest rates have a significant effect on the stock price index on the Indonesia Stock Exchange, inflation with a significance level of 0.007 < 0.05 for the interest rate with a significance level of 0.000 < 0.05 and the exchange rate with a significance level of 0.126 > 0 , 05 then the exchange rate has no significant effect on the stock price index on the Indonesia Stock Exchange. Simultaneously, inflation, interest rates and exchange rates have a significant effect on the stock price index on the Indonesia Stock Exchange.